Study of Type and Antimicrobial Resistance in Sternal Wound Infection Following Coronary Artery Bypass Graft Surgery - Jamshid Faghri; Mohammad Javad Mollakoochekian; Sharareh Moghim; Bahram Nasr-Esfahani; Nafiseh-Sadat Hosseini; Golfam Oryan (مجله دانشکده پزشکی اصفهان, 2013)
Background: Sternal ulcer infections have a great importance and complexity following coronary artery bypass graft (CABG) surgery. Although this kind of infection has a low prevalence but the complications are severe. The purpose of this study was to determine the type of microorganism and antibacterial resistance in sternal wound infections following CABG surgery in Shahid Chamran hospital in Isfahan, Iran, from 2009 to 2012.